Pengaruh Literasi Digital dan Persepsi Return dan Risiko dalam Meningkatkan Minat Investasi Generasi Z di Pasar Modal pada Era New Normal - Deasy Lestary Kusnandar; Dewi Permata Sari; Nana Sahroni (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
This study aims to determine the effect of digital literacy and perceptions of returns and risks on investment intentions in generation z. This research is a type of quantitative research using survey methods given to Zenial Genaration. Sampling in this study was 112 respondents with the sampling method used was judgment sampling. The measuring instrument in this study uses an interval scale of 1-5. Respondents gave answers in the range of answers from strongly disagree to strongly agree. Then, the analysis used is Regression Analysis. This analysis is assisted by using the SPSS program.The results of this study indicate that digital literacy influences interest in investing in the new normal era in the z generation, as well as the perception of returns and risks owned by the z generation affects the interest in investing in the capital market in the new normal era.